PENGARUH PENGEMBANGAN KARIER DAN KONDISI PEKERJAAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PELAYANAN PERIZINAN TERPADU KABUPATEN SUKOHARJO - Widiastuti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
This study aims to: 1) To analyze the effect of career development to job satisfaction of employees in the office Integrated Licensing Service Agency Sukoharjo. 2) To analyze the effect of working conditions on the job satisfaction of employees in the office Integrated Licensing Service Agency Sukoharjo. 3) To analyze the effect of job satisfaction on employee performance in office Integrated Licensing Service Agency Sukoharjo. Population and sample used in this study as many as 35 people. While the analysis of the data used in this study include: 1) validity and reliabilit. 2) Analysis of the path (Path Analysis). The results of the study were: 1) Career development has a significant positive effect directly on job satisfaction, career development as well as indirect influence on performance. 2) Kondisi work has a significant positive effect directly to job satisfaction, as well as conditions of employment have an indirect influence on performance. 3) Job satisfaction has a significant positive impact directly on the performance of employees. Keywords: Career Development, Work Conditions, Job Satisfaction, and Performance